Iron-coordinating π-conjugated semiconducting polymer: morphology and charge transport in organic field-effect transistors. Issue 24 (27th May 2020) - St. Onge, P. Blake J.; Chen, Tzu-Chien; Langlois, Adam; Younus, Aneeta; Jo Hai, I; Lin, Bi-Hsuan; Chiu, Yu-Cheng; Rondeau-Gagné, Simon
Abstract : A new approach to improve charge transport and solid-state morphology in a semiconducting polymer was developed through metal coordination without disruption of the π-conjugation. Abstract : A rational side-chain engineering was performed on a semicrystalline semiconducting conjugated polymer based on diketopyrrolopyrrole (DPP) to incorporate metal-chelating moieties without disruption of the π-conjugation. Specifically, a benzimidazole pyridine-based pincer ligand (MeBZIMPY), known to easily coordinate with M(ii ) metal centers, was inserted into the conjugated polymer and the effect of Fe(ii ) coordination on the optical properties was probed by absorption spectroscopy. Moreover, a careful analysis was performed on the metallopolymer in the solid state by grazing incidence X-ray diffraction and atomic force microscopy to evaluate the effect of coordination on the nanoscale morphology and chain packing. Coordination of Fe was directly confirmed by X-ray fluorescence spectroscopy and X-ray near edge absorption spectroscopy experiments. The resulting semiconducting metallopolymer was shown to possess a good solubility in common organic solvents after complexation and a smooth morphology at the nanoscale. The electronic properties of the new metallopolymer were evaluated through fabrication of organic field-effect transistors (OFETs). Interestingly, coordination of Fe(ii ) by the pincer ligand-containing DPP polymer was shown to enhance the charge mobility in organic field-effect transistors, going from 0.84 to 1.18 cm 2 V −1 s −1 upon coordination, which can be directly attributed to the influence of the metal complex on the solid-state morphology. The direct coordination of Fe(ii ) through pincer ligands is a promising strategy to enhance the charge transport and modulate the optoelectronic properties of π-conjugated polymers without the use of π-conjugation breaking units and/or multi-step synthesis.